THE ROLE OF P-GLYCOPROTEIN IN RATIONAL PHARMACOTHERAPY IN CARDIOLOGY - A. V. Shulkin; E. N. Yakusheva; N. M. Popova (Столичная издательская компания, 2015)
On the basis of the analysis of published data the role of P-glycoprotein, carrier protein, in rational pharmacotherapy in cardiology was shown on the example of its substrates - digoxin, antiplatelet agents and anticoagulants. Determination of C3435T polymorphism of multidrug resistance gene (MDR1), encoding P-glycoprotein, in pharmacotherapy with digoxin, antiplatelet drugs (clopidogrel tikagrelol, prasugrel) and anticoagulants (dabigatran etexilate, rivaroxaban, edoxaban) is not feasible in routine practice. Drug in- teractions have clinical implications for the efficacy and safety of pharmacotherapy in coadministration of these drugs with P-glycoprotein substrates, inducers and inhibitors.